A multi-scale urban integrated assessment framework for climate change studies: A flooding application. (May 2019) - Ford, Alistair; Barr, Stuart; Dawson, Richard; Virgo, James; Batty, Michael; Hall, Jim
Abstract: In order to assess the potential future impacts of climate change on urban areas, tools to assist decision-makers to understand future patterns of risk are required. This paper presents a modelling framework to allow the downscaling of national- and regional-scale population and employment projections to local scale land-use changes, providing scenarios of future socio-economic change. A coupled spatial interaction population model and cellular automata land development model produces future urbanisation maps based on planning policy scenarios. The framework is demonstrated on Greater London, UK, with a set of future population and land-use scenarios being tested against flood risk under climate change. The framework is developed in Python using open-source databases and is designed to be transferable to other cities worldwide. Highlights: Urban climate impacts must consider processes of socio-economic change alongside climate change. A multi-scale modelling framework for climate impact assessment is presented and applied to London, UK. Flood risk will increase with future climate change and socio-economic change may increase risk and impacts. Potential adaptation options have trade-offs and co-benefits that can be assessed with the framework.